Prominent Eustachian Valve in Newborns: A Report of Four Cases - Gad, Ashraf; Mannan, Javed; Chhabra, Manoj; Zhang, Xi Xiao Yang; Narula, Pramod; Hoang, Danthanh (American Journal of Perinatology Reports, 2016)
The Eustachian valve (EV) is an embryological remnant of the inferior vena cava that during fetal life helps divert oxygenated blood from the IVC toward the foramen ovale to escape the pulmonary circulation. This remnant usually regresses after birth and is considered a benign finding in the majority of cases. However, EV can lead to complications in the neonatal period or later in life. In this short case series, we present four newborn infants with prominent EV who were symptomatic after birth and required admission to the neonatal intensive care unit.
Keywords: Eustachian valve; newborn; cyanosis; echocardiogram; infant